BIO-OPTICAL CHARACTERISTIC OF CASE-2 COASTAL WATER SUBSTANCES IN INDONESIA COAST - I Ketut Swardika (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2007)
The result of our study in the bio-optical characteristic of mixed water substances or referred as water leaving radiance of chlorophyll-a in case-2 water. Apparent optical properties of chlorophyll-a(chl-a) influence by others water constituents eq.particle backscattering, and yellow substances absorption coefficients. We studied varies Chl-a concentration from 0.001 ug/l,-65.0 ug/l, mixed by suspended particle (SS) concentration from 0.01 mg/l-50.0mg/l, and yellow substances absorption coeficients (ay) from 0.001m - 5.0m. We used the simple radiative transfer equation in seawater method to simulate the Normalized water leaving radiance (NLw)of Chl-a with concentration less than 1 ug/l and less influence from other substances similiar to NLw of pure sea water characteristic. This high reflected at blue band. Otherwise, chl-a concentrations more than 1 ug/l, are similiar to the absorption characteristic of Chl-a with flourescene peak at 680 nm. The Cross characteristic (Hinge point) occurs at 530 nm. Higher SS concentration causes NLw characteristic of Chl-a change, where hinge point moves toward the longer wavelength. Higher yellow substance absorption coeficients cause NLw characteristic of Chl-a has strange behavior. To keep the NLw Chl-a characteristic SS concentration should be no more than 1 mg/l, and ay coeficient no more than 0.01m. Keyword: bio-optical, chlorophyll, the Normalized water leaving radiance.